INCLUSIVE DIGITAL TRANSFORMATION FOR MSMES: A CAPABILITY-BASED FRAMEWORK FOR SUSTAINABLE ADOPTION - Vip Paramarta; Afferdhy Ariffien (Organisasi Kreatif Indonesia Emas, 2024)
This conceptual paper develops an integrative framework for inclusive digital transformation in micro, small, and medium enterprises (MSMEs). The analysis connects the resource-based view, dynamic capabilities, absorptive capacity, organizational learning, social capital, open innovation, resilience, and entrepreneurial-ecosystem perspectives. It does not claim primary survey, interview, experimental, or statistical data. The synthesis argues that digital readiness, process redesign, data discipline, workforce capability, and ecosystem access should be organized as repeatable managerial routines rather than treated as isolated interventions. The framework proposes staged diagnosis, implementation, evaluation, and learning mechanisms and identifies implications for owner-managers, support organizations, and future empirical research.